Recent reports on dissociative identity disorder - Golebiowska, Maria; Golebiowska, Beata; Lin, Yi Shiuan; Wieleba, Malgorzata (Journal of Education, Health and Sport, 2017)
Psychiatric disorders occur more and more frequently nowadays as the result of non-capability of the human mind to keep up with the pace of today’s living models. One of the most unusual way of escaping from the most traumatic experiences in one’s life is the dissociation mechanism, in the most severe cases resulting in dissociative identity disorder. The aim of this study is to present current state of art on the issue of DID and future courses of diagnostics and possible treatment. Within the study, out of 210 articles related to the dissociative identity disorder, multiple personality disorder, 12 significant articles were used in the analysis. Dissociative identity disorder is becoming more and more frequent diagnosis in modern psychiatry. For the diagnostic purposes, broad differential diagnostics process has to be applied as DID is related to many other psychiatric conditions, such as schizofrenia or PTSD. Apart from that, DID patients and their personalities suffer from many psychiatric comorbidities, such as depression, anxiety, OCD disorders. Unfortunately, due to the length of the treatment processes, which last for the whole life of the patient, its hard to identify the cases with full integration of identity and full recovery. As a conclusion, authors define DID as an important issue in modern psychiatry which should be further addressed in neurobiological and pharmacological studies.